Augmented reality for intracranial meningioma resection: a mini-review - Gómez Amarillo, Diego F.; Ordóñez-Rubiano, Edgar G.; Ramírez-Sanabria, Andrés D.; Figueredo, Luisa F.; Vargas-Osorio, María P.; Ramon, Juan F.; Mejia, Juan A.; Hakim, Fernando (Frontiers in Neurology, 2023)
Augmented reality (AR) integrates computer-generated content and real-world scenarios. Artificial intelligence's continuous development has allowed AR to be integrated into medicine. Neurosurgery has progressively introduced image-guided technologies. Integration of AR into the operating room has permitted a new perception of neurosurgical diseases, not only for neurosurgical planning, patient positioning, and incision design but also for intraoperative maneuvering and identification of critical neurovascular structures and tumor boundaries. Implementing AR, virtual reality, and mixed reality has introduced neurosurgeons into a new era of artificial interfaces. Meningiomas are the most frequent primary benign tumors commonly related to paramount neurovascular structures and bone landmarks. Integration of preoperative 3D reconstructions used for surgical planning into AR can now be inserted into the microsurgical field, injecting information into head-up displays and microscopes with integrated head-up displays, aiming to guide neurosurgeons intraoperatively to prevent potential injuries. This manuscript aims to provide a mini-review of the usage of AR for intracranial meningioma resection.